The Relationship Between Education and Training on State Civil Apparatus Work Productivity (Case Study at BKPP Office in Yogyakarta City 2018) - Anityaningrum, Ummu; Kurniawan, Bachtiar Dwi (Universitas Muhammadiyah Yogyakarta, 2020)
In the government organizations, human resources are the State Civil Apparatus (ASN), which has an important role in carrying out the main tasks and functions of the bureaucracy. This paper aims to find out the quality and capacity of ASN who are deemed to have not been maximized and have not contributed to public services and bureaucratic performance. The organization needs a human resource management design (HR), so that the organization can utilize HR effectively. Education and training (DIKLAT) is one of the human resource development programs in terms of HRM and one of the efforts to face global challenges in order to build ASN professional development and to increase its competence. The Yogyakarta City BKPP has the task of supporting the implementation of local government affairs based on the principle of autonomy and assistance tasks in the field of staffing and DIKLAT. In the implementation of government affairs and the implementation of tasks and functions of the organization to achieve maximum goals, it is necessary to improve employee performance productivity. The methodology used in this study uses qualitative methods by finding direct findings in the field based on interviews with informants based on indicators related to this research. Findings from all indicators related to DIKLAT and Productivity indicate that DIKLAT is related to ASN productivity in BKPP especially in terms of quality, quantity, and timeliness. In fact, in terms of attitude, it is not too closely related to DIKLAT because it is influenced by self-awareness and habits of each individual. In addition, the findings show that employee productivity is also influenced by Additional Employee Income (TPP).